Siegel and Shuster's Funnyman the first Jewish superhero, from the creators of Superman - Andrae, Thomas; Gordon, Mel 1947-2018; Siegel, Jerry 1914-1996; Shuster, Joe 1914-1992 (Feral House, 2010)
"Here is a kaleidoscopic analysis of Jewish humor as seen through Funnyman, a little-known super-heroic invention by the creators of Superman. Included are complete comic-book stories and daily and Sunday newspaper panels from Jerry Siegel and Joe Shusters creative fiasco"...Provided by publisher
"Inside find reproductions from Funnyman's rare comic books, Sunday funnies, and daily strips"...Back cover. - Includes bibliographical references (p. 82-83)
Keywords: Siegel, Jerry -- 1914-1996; Shuster, Joe -- 1914-1992; Funnyman (Fictitious character); Comic books, strips, etc -- United States -- History and criticism; Superheroes; Jewish cartoonists -- United States -- Biography; Jewish wit and humor -- History and criticism